Studi Perbandingan Pelaksanaan Fungsi Legislasi oleh Dewan Perwakilan Daerah Dikaitkan dengan Teori Pemisahan Kekuasaan antara Indonesia dan Amerika Serikat - Fauzia Artifani; Anajeng Esri Edhi Mahanani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
As a state of law, legislative power has an important role for Indonesia and the United States. Legislative power has the main function to form a law/law or what is commonly called the legislative function. The implementation of the legislative function in Indonesia and the United States has differences related to the implementation of the bicameral system and the separation of powers applied in each country. The bicameral system adopted in Indonesia is a weak bicameral system, which means it strengthens the position/authority of one institution over another. In Indonesia, the position and authority of the House of Representatives are greater and stronger than that of the Regional Representative Council as the second chamber, especially when it comes to the function of legislation. Meanwhile, in the United States, a strong bicameral system is applied in which the position and authority of the two chambers (House of Representative and Senate) in legislative power are equally strong and balanced, not biased. The weak authority of the Regional Representatives Council in the legislative function is also influenced by the poor application of the principle of checks and balances in the separation of powers in Indonesia. Therefore, there are several conditions that can be used as comparisons for the implementation of the legislative function in Indonesia and the United States, especially on the differences in the authority given to the institution concerned. The research method used is for normative research with comparative, legal and conceptual approaches. The research is based on the literature by reviewing problems from the doctrines of legal experts, legislation and other legal materials. The purpose of this study was to determine the differences in the implementation of the legislative function of the legislative body in Indonesia and the United States and to find out the relationship between the weak role of the Regional Representatives Council in the legislative function and the theory of separation of powers applied in Indonesia